Pengaruh Kebijakan Deviden, Ukuran Perusahaan dan Kebijakan Hutang Terhadap Nilai Perusahaan Yang Tergabung Dalam Jakarta Islamic Indeks di Bursa Efek Indonesia Tahun 2014-2018 - Oktia Gusti; Abel Tasman (Jurnal Salingka Nagari, 2023)
This study aims to analyze : The effect of dividend policy, firm size and debt policy on the firm value in the Jakarta Islamic Index on the Indonesia Stock Exchange (Bursa Efek Indonesia : BEI) in 2014-2018, The effect of dividend policy on the firm value in Jakarta Islamic Index on the IDX in 2014-2018, The effect of firm size on the firm value in Jakarta Islamic Index on the IDX in 2014-2018, The effect of debt policy on the firm value in Jakarta Islamic Index on the IDX in 2014-2018. The Population in this study are companies that are members of the Jakarta Islamic Index on the Indonesia Stock Exchange in 2014-2018. The sample in this study were 12 companies that were determined by the purposive sampling method. The result show that: dividend policy, firm size and debt policy have a significant effect on firm value at companies, dividend policy has a significant positive effect on firm value at companies, firm size has a significant negative effect on firm value in companies, debt policy has a significant positive effect on firm value in companies. In this study, it is suggested that companies should be more careful in using corporate debt so that the company value is more stable and shows the best value.